An APS with 2-D winner-take-all selection employing adaptive spatial filtering and false alarm reduction. - Fish, A.
An active pixel sensor (APS) with two-dimensional winner-take-all (WTA) detection is presented. This system-on-a-chip employs adaptive spatial filtering of the processed image, with bad pixel elimination and false alarm reduction in case of a missing object. The circuit has a unique ability of adaptive spatial filtering that allows removal of the background from the image, one stage before it is transferred to the WTA detection circuit. A test chip of a 64*64 array has been implemented in 0.5-μm CMOS technology, has a 49% fill factor, is operated by a 3.3-V supply, and dissipates 36 mW at video rate. System architecture and operation are discussed and measurements from the prototype chip are presented.
Keywords: 0.5 micron; 2D winner-take-all selection; 3.3 V; 36 mW; APS; CMOS; VLSI; Active pixel sensor; Adaptive spatial filtering; Bad pixel elimination; False alarm reduction; Fill factor; System architecture; Test chip